Cardiac Arrhythmias in Athletes and Their Impact on Health and Sports Participation: A Narrative Review - Orłowska, Maria; Przepióra, Agnieszka; Żmigrodzka, Anna; Kozłowska, Jana; Sanocka, Maria; Wielogórska, Aleksandra; Kamińska, Agnieszka; Kwiatkowska, Anna; Czernic-Goławska, Klaudia; Falana, Joanna; Trojnar, Karolina (Quality in Sport, 2026)
Background: Sport and physical activity induce structural, functional, and electrical adaptations of the heart, known as the “athlete’s heart.” Although usually physiological, these changes may overlap with pathological conditions and increase susceptibility to arrhythmias, including sudden cardiac death (SCD). Endurance and mixed sports particularly affect cardiac remodeling and electrophysiology. Aim: To summarize common cardiac arrhythmias in athletes, describe their mechanisms, and discuss clinical implications for diagnosis, management, and prevention of sudden cardiac events. Materials and Methods: A literature review was conducted based on recent studies and meta-analyses on cardiac adaptations and arrhythmias in athletes. Key topics included sinus bradycardia, atrioventricular (AV) block, premature ventricular contractions (PVCs), atrial fibrillation (AF), and arrhythmias linked to SCD, such as long QT syndrome, Brugada syndrome, Wolff–Parkinson–White syndrome, and arrhythmogenic right ventricular cardiomyopathy. Results: Sinus bradycardia and AV block are common in endurance athletes and are mainly related to increased vagal tone. PVCs are usually benign but require evaluation. AF is more prevalent in endurance athletes and is associated with atrial enlargement and fibrosis. Rare arrhythmias related to channelopathies and cardiomyopathies significantly contribute to SCD risk. Diagnosis includes ECG, echocardiography, Holter monitoring, exercise testing, and cardiac MRI. Management ranges from observation to pharmacological therapy or invasive procedures. Conclusions: Regular monitoring is essential to distinguish physiological adaptations from pathological arrhythmias. Early diagnosis and individualized management enable safe sports participation and reduce SCD risk.